HER2/neu Oncogene Silencing in a Breast Cancer Cell Model Using Cationic Lipid-Based Delivery Systems - Adhika Balgobind; Aliscia Daniels; Mario Ariatti; Moganavelli Singh (MDPI AG, 2023)
The overexpression of the human epidermal growth factor 2 (HER2/neu) oncogene is predictive of adverse breast cancer prognosis. Silencing the HER2/neu overexpression using siRNA may be an effective treatment strategy. Major requirements for siRNA-based therapy are safe, stable, and efficient delivery systems to channel siRNA into target cells. This study assessed the efficacy of cationic lipid-based systems for the delivery of siRNA. Cationic liposomes were formulated with equimolar ratios of the respective cholesteryl cytofectins, 3β-N-(N', N'-dimethylaminopropyl)-carbamoyl cholesterol (Chol-T) or N, N-dimethylaminopropylaminylsuccinylcholesterylformylhydrazide (MS09), with the neutral helper lipid, dioleoylphosphatidylethanolamine (DOPE), with and without a polyethylene glycol stabilizer. All cationic liposomes efficiently bound, compacted, and protected the therapeutic siRNA against nuclease degradation. Liposomes and siRNA lipoplexes were spherical, <200 nm in size, with moderate particle size distributions (PDI < 0.4). The siRNA lipoplexes exhibited minimal dose-dependent cytotoxicity and effective HER2/neu siRNA transfection in the HER2/neu overexpressing SKBR-3 cells. The non-PEGylated Chol-T-siRNA lipoplexes induced the highest HER2/neu silencing at the mRNA (10000-fold decrease) and protein levels (>111.6-fold decrease), surpassing that of commercially available Lipofectamine 3000 (4.1-fold reduction in mRNA expression). These cationic liposomes are suitable carriers of HER2/neu siRNA for gene silencing in breast cancer.